Bio-deterioration of sweet potato (ipomoea batatas lam) in storage, inoculation-induced quality changes, and control by modified atmosphere - Oyeyipo Olutimilehin Olaitan (Journal of Applied Sciences and Environmental Management, 2013)
The biodeterioration of sweet potato (Ipomoea batatas) was investigated at Port Harcourt, south southern Nigeria. Aspergillus niger, Fusarium oxysporum, Rhizopus stolonifer, Botryodiplodia theobroma and Penicillium sp. were found to be associated with deteriorating sweet potato tubers and used for inoculation of fresh sweet potato samples. The four prevalent isolates (Aspergillus niger, Fusarium oxysporum Botryodiplodia theobroma and Rhizopus stolonifer) were each used to inoculate other sweet potato samples. Storage of samples in modified atmospheres and the effects of inoculation on quality changes were also evaluated. Modified atmospheres created by packing the samples inside a polythene bag of 18μm thickness significantly maintained the quality of the samples. Inoculation of samples with the four prevalent rot fungi significantly (p = 0.05) increased crude protein, lipid and ash content. In contrast, there was a significant decrease in carbohydrate and moisture content when compared with the controls. Modified atmosphere is therefore recommended for control of sweet potato rots and extension of storage life.